If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 = 4b + 18 Reorder the terms: 56 = 18 + 4b Solving 56 = 18 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 56 + -4b = 18 + 4b + -4b Combine like terms: 4b + -4b = 0 56 + -4b = 18 + 0 56 + -4b = 18 Add '-56' to each side of the equation. 56 + -56 + -4b = 18 + -56 Combine like terms: 56 + -56 = 0 0 + -4b = 18 + -56 -4b = 18 + -56 Combine like terms: 18 + -56 = -38 -4b = -38 Divide each side by '-4'. b = 9.5 Simplifying b = 9.5
| x=16+y | | (8(6+7))(8(6+7))(8(6+7))(8(6+7))(8(6+7))(8(6+7))(8(6+7))(8(6+7))(8(6+7))=x | | 16-4x=1(1-x) | | 7=11-v | | 12a-5=43 | | 9z+6+3z=90 | | 6m-6=4m-10 | | 0.7(4x+8)=-1.3(x+2) | | (2x)*(3x)=96 | | -3x+8-5x=21-8x | | -15-6x-7= | | (2x)x(3x)=96 | | 4+6x(6-2)= | | 4-2d= | | -1+3m+12= | | y=-4(-3)-12 | | 1=(2x+45) | | Log(x)=-7 | | 6x-4+8x-12=180 | | 3n+3+24n= | | (2p-5)+(p+2)=45 | | 2x+5=113 | | (2ab^2)(3ab)=x | | 5+3=12t | | 6t-7=53 | | 5b+6=-1 | | (-8x+1)-(7x-1)= | | 5x^2+5y^2-40x-20y-25=0 | | 2z-14=-49+9z | | X-0.25x=79.63 | | -3p-8-4p= | | 5a-6=8a-9 |